Incremental prognostic value of isocitrate dehydrogenase status and O⁶-Methylguanine-DNA methyltransferase promoter methylation beyond World Health Organization grade in adult diffuse glioma: A real-world cohort study - Berkay Ayhan; Ayhan Tekiner; Mehmet Emre Yıldırım; Haydar Çelik; Burak Yürük; Serdar Cengiz; Kemal Kantarcı; Zeliha Çulcu; Tuncer Taşcıoğlu; Koray Öztürk; Yavuz Erdem (Medical Journal of Western Black Sea, 2026)
Aim: Prognostic counseling in adult diffuse glioma increasingly combines histologic grading with routinely available molecular testing. We assessed the incremental prognostic contribution of isocitrate dehydrogenase (IDH) status and O⁶-methylguanine-DNA methyltransferase (MGMT) promoter methylation beyond clinical variables and World Health Organization (WHO) grade in routine neuro-oncology practice.Material and Methods: We conducted a retrospective single-center cohort study of 82 adults who underwent surgery between 2017 and 2022. Three prespecified nested Cox models compared clinical and surgical variables alone, the same variables plus grade, and the full model plus molecular markers. Discrimination, calibration, reclassification, bootstrap optimism correction, and a prespecified subgroup analysis restricted to IDH-wildtype tumors were evaluated. Results: Apparent concordance improved from 0.738 to 0.878 to 0.885, with optimism-corrected values of 0.701, 0.829, and 0.834. WHO grade provided the main improvement in discrimination. Adding IDH and MGMT beyond grade yielded only a small and statistically uncertain increase. IDH-wildtype status remained the dominant adverse molecular feature, whereas no independent prognostic association of MGMT methylation was detected in either the mixed cohort or the IDH-wildtype subgroup.Conclusion: In this real-world cohort, grade and IDH status formed the principal prognostic framework, whereas the additional contribution of MGMT methylation to baseline risk discrimination remained uncertain. These findings are most relevant to resource-variable settings in which comprehensive molecular profiling is not uniformly available.